The Synthesis of Nanostructured Ni5P4 Films and their Use as a Non-Noble Bifunctional Electrocatalyst for Full Water Splitting - Ledendecker, Marc; Calderon, Sandra Krick; Papp, Christian; Steinrück, Hans-Peter; Antonietti, Markus; Shalom, Menny (Angewandte Chemie International Edition, 2015)
The investigation of nickel phosphide (Ni5P4) as a catalyst for the hydrogen (HER) and oxygen evolution reaction (OER) in strong acidic and alkaline environment is described. The catalyst can be grown in a 3D hierarchical structure directly on a nickel substrate, thus making it an ideal candidate for practical water splitting devices. The activity of the catalyst towards the HER, together with its high stability especially in acidic solution, makes it one of the best non-noble materials described to date. Furthermore, Ni5P4 was investigated in the OER and showed activity superior to pristine nickel or platinum. The practical relevance of Ni5P4 as a bifunctional catalyst for the overall water splitting reaction was demonstrated, with 10 mA cm(-2) achieved below 1.7 V.
Keywords: ceramics; hydrogen evolution reaction; nickel phosphides; oxygen evolution reaction; water splitting reaction